1987
DOI: 10.1111/j.1748-5827.1987.tb01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light biomicroscopic observations on the pre‐corneal tear film. 3. The normal tear film of the cat

Abstract: Polarized light biomicroscopy was used to examine the pre‐corneal tear film in 14 normal cats. Blink rates were also determined. The normal range of surface morphology of the feline tear film was established. Two principal categories of surface patterning of the lipid layer of the tear film were identified. These occurred in all eyes examined and were: (a) a wave‐like pattern, and (b) a pattern of variable character resembling the polished surface of granite. Over most of the area of the tear film, the thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
(1 reference statement)
0
13
0
1
Order By: Relevance
“…Accelerated tear BUTs of less than 5 s and histological confirmation of conjunctival GC deficiencies have been reported in three dogs 5 . One study reported tear film stability for up to 9 min in one cat 33 . To the authors’ knowledge, there are no reported mean tear BUTs for normal cats.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Accelerated tear BUTs of less than 5 s and histological confirmation of conjunctival GC deficiencies have been reported in three dogs 5 . One study reported tear film stability for up to 9 min in one cat 33 . To the authors’ knowledge, there are no reported mean tear BUTs for normal cats.…”
Section: Discussionmentioning
confidence: 91%
“…5 One study reported tear film stability for up to 9 min in one cat. 33 To the authors' knowledge, there are no reported mean tear BUTs for normal cats. However, average tear BUTs of less than 3 s OU coupled with the histological evidence of moderately to markedly diminished GCs compared with the normal controls and return of normal GC counts after topical mucinomimetic therapy confirmed GC atrophy in these cats.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with tear film BUTs in normal young beagles (19.7 ± 5 s), 6 tear film BUT was slightly more rapid in our young domestic cats (16.7 ± 4.5 s). This variation in results may be due, in part, to variations in tear film composition, 23–25 and hence, tear film stability of cats compared with dogs. In addition, the technique employed to assess tear film BUTs varied between the canine and our feline studies.…”
Section: Discussionmentioning
confidence: 99%
“…Excision of the majority of meibomian glandular tissue might be expected to lead to problems with an inadequate lipid component of the precorneal tear film. Polarized light biomicroscopy would be one way of attempting to assess the effects of this procedure on qualitative tear film properties 12 …”
Section: Discussionmentioning
confidence: 99%